School Buildings in Rubble Stone Masonry With Cement Mortar in Seismic Areas: Literature Review of Seismic Codes, Technical Norms and Practical Manuals - Schildkamp, Martijn; Araki, Yoshikazu (Frontiers in Built Environment, 2019)
A literature review was carried out with the aim to determine the current state-of-the-art with regards to non-engineered stone masonry in seismic areas. Specific search criteria and definitions were determined for school buildings with loadbearing walls of rubble stone masonry in cement mortar, nominally tied with horizontal reinforcements. A total of 47 relevant field manuals between 1972 and 2017 were analyzed for eligibility and checked for compatibility with the national building codes. An overview was created of similarities, contradictions, gaps and differences between the publications. As the majority of the practical manuals target the Himalayan context, the most relevant codes for the comparison were the Indian and Nepali seismic and building codes. Only 9 manuals describe design and construction processes for schools, even though this conflicts with the codes which specifically prohibit the use of stone masonry for buildings with importance factor 1.5 or higher. It was noticed that 7 out of 9 manuals are (co-)written by the same author, and that the available knowledge, which is largely based on empirical evidence, can be traced back to just a few main sources. However, no consistency nor consensus was found on almost all key topics, such as main dimensions, openings and reinforcing elements. Also, the same illustrations and tables are copied over and over again, including apparent conflicts between the details. The fact that this has never been rectified, as well as the fact that the Indian and Nepali seismic codes have not been properly updated since 1994, are indications that the knowledge has not evolved much since the 1980's. It is concluded that the available information contains many contradictions and has become ambiguous. This raises questions about the correctness and actual value of the knowledge. The paper suggest that the existing knowledge must be fully assessed, validated, optimized and complemented by means of the current state-of-the-art for calculating, testing and modeling. To address this, the authors have started an initiative named SMARTnet, and make an appeal to experts and academics worldwide, to exchange their knowledge and to support the project with their time and expertise.